Understanding and managing the risk during transient operations. Issue 4 (14th March 2020) - Vaughen, Bruce K.
Abstract: This paper presents the results from more than 50 incidents attributed in part to the process safety risks associated with abnormal, transient operations during start‐ups and shut‐downs. A transient operation is defined in this paper as the time when the process is in transition between one operating state and another. In particular, the transient operations‐related focus is on the time when equipment is taken from its safe, idle state to its safe operating conditions (a start‐up) and vice versa, when the equipment is then taken back to its safe, idle state (a shut‐down). There are 10 different start‐up and shut‐down operating modes during normal operations, abnormal operations, and emergency operations. The incidents in this review were attributed to weaknesses in administrative controls that did not work as planned and engineering controls that did not perform as expected. Due to these weaknesses, unexpected events occurred, resulting in quick decisions made without adequately understanding the hazards, evaluating the risks, or managing the changes. In many cases, had the asset integrity and reliability program been in place or effective operational readiness review performed before attempting the process restarts, the risks associated with the transient operating mode could have been reduced.